The impact of internet use on the health status of the older adults in China: a chain mediating model of social interaction and physical exercise - Hu, Jiangwei; Mai, Haoxian; Tan, Chunyun; Du, Yingying (Frontiers in Public Health, 2025)
BackgroundAs China’s population aging intensifies, older adults face growing health risks. Internet use, social interaction, and physical exercise significantly impact their health. This study aims to explore the underlying mechanisms of these variables on older adults health.MethodsThis study used data from the 2021 Chinese General Social Survey (CGSS), involving 3,150 urban and rural older adults aged 60–98. The dependent variable was health status, measured by a composite score of self-assessed health, physical health, and mental health. Internet use served as the independent variable. Social interaction and physical exercise were the mediators. A chain mediation model linking internet use, social interaction, physical exercise, and health status was created. The relationships between these factors were tested using Pearson correlation analysis, multiple linear regression, and Bootstrap.ResultInternet use demonstrated a significant positive impact on older adults’ health status (β = 0.086, p < 0.001), which supports the hypothesis that Internet use improves health outcomes. The total indirect effect of the chain mediation model was 0.0165 (95% CI = [0.0103, 0.0239]). Specifically, the indirect effect of the path Internet use → social interaction → health status was 0.0080 (95% CI = [0.0037, 0.0131]), the indirect effect of the path Internet use → physical exercise → health status was 0.0077 (95% CI = [0.0035, 0.0126]), and the indirect effect of the path Internet use → social interaction → physical exercise → health status was 0.0009 (95% CI = [0.0004, 0.0016]). Social interaction and physical exercise partially and chain-mediate the relationship between Internet use and health status in older adults.ConclusionThis study reveals that internet use significantly impacts older adults’ health both directly and indirectly through enhanced social interaction and physical exercise. The government should promote internet adoption among older adults, especially in underserved rural and low-income areas, by enhancing infrastructure and offering inclusive digital training. Additionally, financial support and policy incentives should be provided to encourage the development of age-friendly applications focused on social interaction and sports. Policymakers should advance the integration of internet services with geriatric health policies to enhance overall well-being.